Assessing Road Safety Development in European Countries: A Cross-Year Comparative Analysis of a Safety Performance Index - Qiong Bao; Zegang Zhai; Yongjun Shen (Applied Sciences, 2022)
The development of a road safety performance index has been widely accepted as a supportive instrument to evaluate and compare the safety performance in different countries. However, most of the current studies concentrate on the index development for only one year. In other words, there is still a lack of cross-year comparison based on the constructed safety performance index, so as to assess the progress of road safety performance in different countries over time. In this study, by collecting data on four background indicators and seven safety performance indicators of 21 European countries for both 2008 and 2015, the hierarchical clustering analysis is first utilized to identify country groups based on the background indicators. Then, the principal component analysis (PCA) is applied for each group to construct a safety performance index, and a cross-year comparative analysis on country grouping, index ranking, and weight allocation is conducted. The results show that the members in the two country groups remain the same, implying that there was no dramatic change with respect to these countries’ road safety policy context in these two years. However, the gaps between these two country groups with respect to their overall socioeconomic development, as well as their road safety performance, enlarged over this period. Moreover, by comparing the indicator weights assigned for each country group in different years and examining the changes in indicator values of each country, a useful insight into the areas of underperformance is gained, which cannot be revealed in single year index evaluation. All these findings provide policy makers with valuable guidance to prioritize their actions to improve the level of road safety.